Vaccine acceptance in rural India: Engaging faith leaders as vaccine ambassadors - Banerjee, Preetika; Seth, Rajeev; Dhaliwal, Baldeep K.; Sullivan, Alexis; Qiayum, Yawar; Thankachen, Betty; Closser, Svea; Shet, Anita (Frontiers in Public Health, 2022)
Introduction Religious faith is a key marker of identity and shapes community perspectives and trust. Faith leader involvement in vaccine campaigns in India have been beneficial to counter misinformation regarding infectious diseases such as polio. Faith leaders are influential stakeholders who bear potential to enhance public confidence in vaccine campaigns. Context While vaccine coverage has been increasing in India, inequities abound, especially in populations with historically low vaccine confidence. The COVID-19 pandemic has led to major disruptions in delivery of routine immunization services for children. To address these challenges, we co-designed interventions aimed at contextual communication strategies and peer support. Engaging faith leaders was an important part of this intervention. In this report we describe our experience and highlight the perspectives of faith leaders and their expectations of the outcomes for this intervention. Programmatic elements The CIVIC Project, conducted from January to December 2021 aimed to engage caregivers, community health workers and key stakeholders, particularly, faith leaders in co-designing interventions to address vaccine hesitancy in Mewat. The project, deeply rooted in community based participatory research, used a three-E approach (Exploration of community perspectives, Establishment of vaccine trust and awareness, Engagement in vaccine promotion activities) to successfully engage faith leaders in the design and dissemination of media messages advocating for vaccine acceptance and uptake. Lessons learned The involvement of faith leaders in the intervention benefited the community in two ways. First, faith leaders were spotlighted via videos, often disseminating advice and personal anecdotes about vaccines, thus reassuring caregivers and community members who previously expressed distrust in vaccines. Second, involvement of trusted faith leaders provided a platform for a two-way dialogue for the community to openly discuss and address myths and misconceptions regarding vaccines. This project provided the learning that co-creating interventions with faith leaders who are often gatekeepers of close-knit communities can lead to the development of vaccine positive messaging that community members relate with, motivating increased vaccine confidence.